Odor maps in the olfactory cortex - Zou, Zhihua (National Academy of Sciences, 2005)
In the olfactory system, environmental chemicals are deconstructed into neural signals and then reconstructed to form odor perceptions. Much has been learned about odor coding in the olfactory epithelium and bulb, but little is known about how odors are subsequently encoded in the cortex to yield diverse perceptions. Here, we report that the representation of odors by fixed glomeruli in the olfactory bulb is transformed in the cortex into highly distributed and multiplexed odor maps. In the mouse olfactory cortex, individual odorants are represented by subsets of sparsely distributed neurons. Different odorants elicit distinct, but partially overlapping, patterns that are strikingly similar among individuals. With increases in odorant concentration, the representations expand spatially and include additional cortical neurons. Structurally related odorants have highly related representations, suggesting an underlying logic to the mapping of odor identities in the cortex.